Partial Aminoglycoside Lesions in Vestibular Epithelia Reveal Broad Sensory Dysfunction Associated with Modest Hair Cell Loss and Afferent Calyx Retraction - Sultemeier, David R.; Hoffman, Larry F. (Frontiers in Cellular Neuroscience, 2017)
Although the effects of aminoglycoside antibiotics on hair cells have been investigated for decades, their influences on the dendrites of primary afferent neurons have not been widely studied. This is undoubtedly due to the difficulty in disassociating pathology to dendritic processes from that resulting from loss of the presynaptic hair cell. This was overcome in the present investigation through development of a preparation using Chinchilla laniger that enabled direct perilymphatic infusion. Through this strategy we unmasked gentamicin’s potential effects on afferent calyces. The pathophysiology of the vestibular neuroepithelia after post-administration durations of 0.5 through 6 months was assessed using single-neuron electrophysiology, immunohistochemistry, and confocal microscopy. Hair cell densities within cristae central zones (0.5-, 1-, 2- and 6-months) and utricle peri- and extrastriola (6-months) regions were determined, and damage to calretinin-immunoreactive calyces was quantified. Gentamicin-induced hair cell loss exhibited a profile that reflected elimination of a most-sensitive group by 0.5-months post-administration (18.2%), followed by loss of a second group (20.6%) over the subsequent 5.5 months. The total hair cell loss with this gentamicin dose (approx. 38.8%) was less than the estimated fraction of type I hair cells in the chinchilla’s crista central zone (approximately 60%), indicating that viable type I hair cells remained. Extensive lesions to afferent calyces were observed at 0.5-months, though stimulus-evoked modulation was intact at this post-administration time. Widespread compromise to calyx morphology and severe attenuation of stimulus-evoked afferent discharge modulation was found at 1 month post-administration, a condition that persisted in preparations examined through the 6-month post-administration interval. Spontaneous discharge was robust at all post-administration intervals. All calretinin-positive calyces had retracted at 2 and 6 months post-administration. We found no evidence of morphologic or physiologic recovery. These results indicate that gentamicin-induced partial lesions to vestibular epithelia include hair cell loss (ostensibly reflecting an apoptotic effect) that is far less extensive than the compromise to stimulus-evoked afferent discharge modulation and retraction of afferent calyces (reflecting non-apoptotic effects). Additionally, calyx retraction cannot be completely accounted for by loss of type I hair cells, supporting the possibility for direct action of gentamicin on the afferent dendrite.